PS01.232: SHORT-TERM OUTCOMES OF ROBOT-ASSISTED MINIMALLY INVASIVE ESOPHAGECTOMY. (14th September 2018) - He, Haiqi; Fu, Junke; Zhang, Guangjian
Abstract: Background: Surgical resection with radical lymphadenectomy is a pivotal component in the multidisciplinary therapy of esophageal cancer. Minimally invasive esophagectomy was shown to be effective in reducing the morbidity and was adopted increasingly. As a novel minimally invasive technique, robot-assisted esophagectomy remains in the initial stage ofapplication. This study describes the single-institution experience of robotic esophagectomy. Methods: Between March 2016 and October 2017, 20 consecutive patients underwent robot assisted esophagectomy at our institute. The thoracic and abdominal mobilization were all performed with the assistance of the robot. We retrospectively collected the operative data and postoperative outcomes. Results: The majority of patients were male (80%), and the median age was 62 years. The average operative time was 342 minutes (range 280–440). The average blood loss was 112 ml (range 50–400). No patient experienced conversion to a thoracotomy or laparotomy. R0 resection was achieved in all patients, the mean number of dissected lymph nodes was 19 (range 8–32). No 90-day operative mortality was observed, and postoperative complications were present in 8 of 20 patients (40.0%). Pulmonary complications were the most common event and were observed in 3 patients. Two patients experienced an anastomotic leak. Conclusion: Our study demonstrated that robot-assisted esophagectomy is a safe and technically feasible alternative to conventional thoraco-laparoscopic esophagectomy. Disclosure: All authors have declared no conflicts of interest.